Model Daya Saing IKM berbasis Start-Up Business untuk meningkatkan produktivitas Usaha Makanan Khas daerah Tawangmangu - Inge Gunawan; Feliks Dabur; Angga Hendrawan; Wati Br Simanjuntak; Ernita Rosinta Sianturi (Politeknik Ganesha Medan, 2026)
The purpose of this study is to analyze the current condition of traditional food SMEs in Tawangmangu, including their productivity and competitiveness. The research method used is a quantitative approach using the SEM PLS application. The number of samples was 150 respondents. The results of the study showed significant competitiveness potential along with increasing national consumption, but the main challenge is the low innovation of production and marketing processes that are still traditional. The Start-Up Business approach can be a strategic solution to increase productivity and competitiveness, but there is no specific model that integrates the start-up approach into the context of regional SMEs such as Tawangmangu. Increased innovation directly improves performance, buyer interest, and market perception. As a result, the pressure is on the need to increase innovation, especially in production and marketing processes, especially digital strategies to increase the competitiveness of traditional food SMEs in Tawangmangu. The start-up model can be used as an adaptive framework, but it needs to be adapted to the local context and strengthen relevant mediation channels to have an impact on performance and market demand.